WDS-Modality: A Physics-Informed Multi-Modal Agent Framework for Resilient Water Distribution System Assessment Using Large Language Models without Fine-tuning - Tianwei Mu; Yue Wang; Manhong Huang; Mingzhe Yuan; Dan Xue; Wenhong Wang; Hui Yang; Jun Li; Bo Zhou (Water Research, 2026)

Oral immunization of Nile tilapia with Chlorella-bioencapsulated multi-epitope fusion antigen effectively protects against Streptococcus agalactiae infection - Xiaodong Deng; Zichun Xiao; Dan Mu; Dianlong Xu; Juncai Li; Yuxuan Yang; Hanjie Gu; Yonghua Hu; Xiaowen Fei (Fish & Shellfish Immunology, 2026)

Nitric acid-modified co-pyrolyzed biochar from gentamicin mycelial residue and biomass regulates cattle manure composting: Reducing carbon loss and enhancing humification - Yingjin Song; Huiling Niu; Yamei Zeng; Guanyi Chen; Zeng Dan; Beibei Yan; Lan Mu; Yuxing Luo; Yinjie Zhong; Sheng Xu; Qingyi Li; Anna Jin (Journal of Environmental Management, 2026)

Anchoring MoOx nanodots in N-doped porous carbon via a biomimetic strategy: enhanced supercapacitor performance - Li Li; Shou-Cheng Jiao; Chang-Wang Shao; Yu-Man Li; Long-Yu Zhang; Xing-Shun Cong; Xian-Yong Wei; Dan Mu (Fuel, 2026)

Insights into the molecular basis of umami in premium green teas via integrated metabolomics, peptidomics, and in silico molecular docking - Jiaqi Yang; Shitao Fang; Qi Zhou; Yizhi Wang; Kangni Yan; Peng Qunhua; Lin Zhi; Wu Yan; Fu Jianyu; Mu Dan; Lv Haipeng; Shi Jiang (Food Chemistry, 2026)

CNTN6 Modulates Slit-Robo Signaling in Cortical GABAergic Interneuron Migration - Yiliang Xu; Tian Zhao; Dan Zhao; Wei Zhang; Di Mu; Ailing Gui; Junzhi Guo; Kazutada Watanabe; Zhi-Cheng Xiao; Haihong Ye (Neuroscience Bulletin, 2026)

Effects of Dietary Macleaya cordata Extract on Growth Performance, Antioxidant Capacity, Immunity, and Stress Resistance in Juvenile Red Claw Crayfish (Cherax quadricarinatus) - Fan-Le Jia; Yao-Peng Lu; Ze-Long Zhang; Xiu-Xia Zhang; Pei-Hua Zheng; Jun-Tao Li; Ying-Hui Liang; Dan Mu; Jian-An Xian (Fishes, 2026)
High-density, intensive aquaculture has led to the deterioration of the aquatic environment, which compromises the survival, immune function and disease resistance of aquatic animals. This study investigated the effects of dietary supplementation with different levels of Macleaya cordata extract (MCE) on growth performance, muscle composition, antioxidant capacity, immune function, and stress resistance in red claw crayfish (Cherax quadricarinatus). Juvenile crayfish with an initial body weight of 0.22 ± 0.02 g were fed diets supplemented with 0 (Diet 1, Control), 0.01 (Diet 2), 0.02 (Diet 3), 0.04 (Diet 4), 0.08 (Diet 5), and 0.15 (Diet 6) g/kg MCE for eight weeks. Results showed that dietary MCE supplementation had no significant effect on the growth performance or muscle composition of crayfish. Conversely, supplementation with 0.02–0.04 g/kg MCE significantly increased the activities of superoxide dismutase (SOD), glutathione peroxidase (GPx), phenoloxidase (PO), and the total antioxidant capacity (T-AOC) in the hepatopancreas and plasma, while significantly reducing malondialdehyde (MDA) levels. Specifically, supplementation with 0.04 g/kg MCE significantly upregulated the hepatopancreatic mRNA expression levels of SOD, hemocyanin, GPx, and selenium-dependent glutathione peroxidase (Se-GPx). Furthermore, the challenge test demonstrated that supplementation with 0.04 g/kg MCE significantly improved crayfish survival under microcystin-LR (MC-LR) stress. Overall, supplementation with 0.04 g/kg MCE significantly improved the antioxidant capacity, immunity, and stress resistance of crayfish, suggesting its potential as an environmentally friendly immunostimulatory feed additive to protect against MC-LR stress in crayfish.

A systematic identification and characterization of long noncoding RNAs during abiotic stress in Medicago truncatula - Kanghua Du; Yingan Zhu; Weiyu Yan; Ting Gao; Wanfu Mu; Ziwei Zhao; Zhong Dan; Xiaolu Meng; Haoting Chen; Yan Zhao; Jie Zhang (Journal of Plant Physiology, 2026)

In-plane macro/meso-porous structured MXene film constructed by in situ solvothermal etching method with superior capacitive performance - Yesheng Wang; Leling Song; Jixin Wang; Dandan Zhu; Jinghua Wang; Yanbiao Ren; Dan Mu; Yanxin Yu (Chemical Engineering Journal, 2026)

Ailancoumaquinone A and ailancoumarins M-T, undescribed terpenylated coumarins from Ailanthus altissima and their anti-inflammatory activity - Da-Le Guo; Li Huang; Hui-Min Zhang; Yu-Ting Mu; Hao-Ran Lei; Li-Lian Zhao; Su Hu; Yun-Jie Hu; Cong-Cong Li; Meng-Dan Liu; Yu-Cheng Gu; Guan-Kui Yang; et al. (Phytochemistry, 2026)

Biomass-derived N and P co-doped carbon-supported Pd catalyst for efficient CO2 hydrogenation to formate - Dan Zhang; Maowei Luo; Xianming Zhu; Faisal Irshad; Hamzah A.S.M. Yaseen; Chao Mu; Yong Wang; Shengping Wang; Xinbin Ma (Fuel, 2026)

Detecting and comparing extinction debts of amphibians in China under climate change - Yu-Xiao He; You-Hua Chen; Xiao-Qin Shi; Chao-Sheng Mu; Dan-Dan Yu; Jia-Qi Li; Hai-Gen Xu; Jian-Ping Jiang (Biological Conservation, 2026)

Impact of salinity on nitrogen cycling and microbial community functional potential in groundwater of the Yellow river delta - Huan Wang; Chuanshun Zhi; Yufei Jiao; Dan Xu; Wenfeng Gao; Yawei Kou; Xiancang Wu; Jing Bai; Hui Mu; Houliang Lu; Xiaonong Hu (Applied Geochemistry, 2026)

Signaling pathways and potential therapeutic agents in trastuzumab-induced cardiotoxicity - Haonan Zhang; Changxu Lu; Siyuan Cheng; Jingyi Wu; Anqi Hu; Zhongyi Mu; Dan Dong; Mingli Sun (Apoptosis, 2026)

Transformation of chloroxylenol in real sewer sediments: Key adsorption sites and CYP450-catalyzed biodegradation - Xinhui Xia; Yujia Du; Huizhi Mu; Dan Li; Shuocheng Shao; Qingliang Zhao; Liangliang Wei (Journal of Hazardous Materials, 2025)

Laccase-mimicking chiral Cu-nanozymes for enantioselective catalysis of phenolic substrates - Qiaodan Du; Zhihao Mu; Dan Liang; Xinman Han; Yuan Zhao; Wei Ma (Journal of Hazardous Materials, 2025)

Interface modification of fluopyram-loaded microcapsules using Fe3+/lignosulfonate via coordination and electrostatic interactions to improve nematicide rhizosphere utilization - Haichao Cao; Yanhou Zhao; Jiangzhou Li; Kuai Dai; Lijun Jiang; Wenzheng Ling; Wei Mu; Chao Feng; Dan Chen; Jinguang Yang (Chemical Engineering Journal, 2025)

Ubiquitination: A non-negligible modulator in doxorubicin-induced cardiotoxicity - Can Gao; Changxu Lu; Jinwen Wei; Zhongyi Mu; Mingli Sun; Dan Dong; Zhenning Liu (Chemico-Biological Interactions, 2025)

Interlayer covalent bridging covalent organic polymers for highly efficient photocatalytic organic synthesis - Xia Zhao; Ai-Cen Li; Dan Yang; Yong-Hui Wang; Xin Mu; Cong Wang; Hua-Qiao Tan (Chemical Engineering Journal, 2025)

Comparative analysis of rural organic waste treatment: greenhouse gas emissions, economics, and energy flow - Hao Peng; Lan Mu; Yingjin Song; Dan Zeng; Hong Su; Zhanjun Cheng; Rundong Li; Guanyi Chen (Biomass and Bioenergy, 2025)

The combined damage of bisphenol A and high fat diet to learning and memory in young male mice: the regulatory effect of BDNF/TrkB/PI3K/AKT pathway on autophagy - Jinshi Li; Dan Wu; Yuyang Mu; Yunzhu Wang; Lingling Zhai; Lihong Jia (Environmental Research, 2025)

Could chloroxylenol be used as WBE biomarker in gravity sewers? Fates, behaviors and feasible conditions - Xinhui Xia; Huizhi Mu; Yujia Du; Shuocheng Shao; Yaqun Li; Dan Li; Qingliang Zhao; Liangliang Wei (Water Research, 2025)

Characterization and anti-inflammatory investigation of sesquiterpene lactones from Ixeris chinensis - Shaoqiang Fan; Jia Chen; Zhuo Zhang; Guohua Gong; Yu Mu; Dongsong Bai; Dan Zheng; Xueshi Huang; Liya Li (Phytochemistry, 2025)

Deciphering the key role of biofilm and mechanisms in high-strength nitrogen removal within the anammox coupled partial S0-driven autotrophic denitrification system - Shuyan Yin; Yi-Xuan Wang; Cheng Hou; Jing Wang; Jing Xu; Xinbai Jiang; Dan Chen; Yang Mu; Jinyou Shen (Bioresource Technology, 2025)

Immobilization and transformation behavior of V(IV) and V(V) by ferrihydrite and lepidocrocite - Jia-li Li; Chun-dan Gan; Xin-yue Du; Yan-li Ren; Mu-cheng Xu; Jin-yan Yang (Process Safety and Environmental Protection, 2025)

Protonated polyethyleneimine enables synchronous crosslinking of polyimide nanofiltration membranes for dye desalination - Qing Fang; Sudan Lan; Xiuxiu Mu; Yanping Zhang; Ya Li; Yajuan Wang; Lihui Yao; Yuyun Chen; Dan Qiu; Linghui Wang (Desalination, 2024)

Exploring of laccase-like nanozyme and membrane filters for efficient removal of tetracycline hydrochloride - Yun Wang; Dan Wang; Qixuan Mu; Yanke Zhai; Jun Hai; Yibing Ji; Ruijun Li (Chemical Engineering Journal, 2024)

The effect of circulating cytokines on the risk of systemic lupus erythematosus: Mendelian randomization and observational study - Dan Xue; Yu Qian; Xiao Tu; Mu He; Fengling Xing; Yunqing Ren; Chengda Yuan (Immunogenetics, 2024)

Enhanced anaerobic reduction of nitrobenzene under hypersaline fluctuation: Glycine betaine metabolism and microbial osmoadaptation mechanisms - Yan Xia; Qian Huang; Xinbai Jiang; Yuxuan Wang; Shuaishuai Guo; Dan Chen; Yang Mu; Jinyou Shen (Chemical Engineering Journal, 2024)

Seasonal simulation and source apportionment of SO42− with integration of major highlighted chemical pathways in WRF-Chem model in the NCP - Xiaoxi Zhao; Xiujuan Zhao; Dan Chen; Jing Xu; Yujing Mu; Bo Hu (Atmospheric Pollution Research, 2024)

Caseinate-coated zein nanoparticles as potential delivery vehicles for guavinoside B from guava: Molecular interactions and encapsulation properties - Haoning Yang; Yu Mu; Dan Zheng; Tess Puopolo; Lejie Zhang; Zhuo Zhang; Sai Gao; Navindra P. Seeram; Hang Ma; Xueshi Huang; Liya Li (Food Chemistry, 2024)

SIRT1-Mediated HMGB1 Deacetylation Suppresses Neutrophil Extracellular Traps Related to Blood–Brain Barrier Impairment After Cerebral Venous Thrombosis - Shuwen Mu; Ziqi Li; Long Lin; Di Wang; Fei Yang; Li Chen; Liang Xian; Kunzhe Lin; Yinghong Lin; Dan Ye; Yang Yang; Liangfeng Wei; et al. (Molecular Neurobiology, 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

Assessing shorebird mortalities due to razor clam aquaculture at key migratory stopover sites in southeastern China - Dan Liang; Tong Mu; Ziyou Yang; Xingli Giam; Yudi Wang; Jing Li; Shangxiao Cai; Xuelian Zhang; Yixiao Wang; Yang Liu; David S. Wilcove (Conservation Biology, 2024)
Aquaculture can provide foraging habitat for birds, but it can also result in intentional and accidental mortality. We examined an overlooked conflict between razor clam ( Sinonovacula spp.) aquaculture and declining shorebirds in southeastern China's Fujian and Zhejiang provinces. We surveyed 6 out of 11 internationally important stopover sites for these shorebirds and monitored shorebird mortality in 2 sites (Xinghua Bay, Yueqing Bay) with razor clam aquaculture. We visited an additional 32 sites in these 2 provinces to determine if there was netting in other razor clam farms. Approximately 8–9 km 2 of intertidal foraging habitat was covered by horizontal nets to prevent birds from feeding on young razor clams at Xinghua Bay and Yueqing Bay. We conservatively estimated that 13,676 (2.5th–97.5th percentile 8,330–21,285) individual shorebirds were entangled in the nets at the 2 monitored sites in April and May 2021, including 2 endangered and 7 near‐threatened species. Mortality of 5 species for which we had sufficient data accounted for 0.76% (black‐tailed godwit [ Limosa limosa ]) to 4.27% (terek sandpiper [ Xenus cinereus ]) of their total flyway populations. This level of mortality could strongly affect their populations. We found netting at 17 additional razor clam farms, indicating a widespread threat to shorebirds. Although razor clams are typically harvested in late March to early April, nets are left on the mudflats throughout the spring and summer, including when the bulk of shorebird migration takes place. Immediately removing these nets after the clam harvest could prevent most of the spring mortality of shorebirds, although this is unlikely to happen without government regulations or economic incentives. To better assess and mitigate the impacts of this conflict, future research should quantify shorebird mortality at other razor clam farms, including during winter, explore less harmful deterrence methods, and assess the socioeconomic factors driving the conflict.

Insights into major pigment accumulation and (non)enzymatic degradations and conjugations to characterized flavors during intelligent black tea processing - Yongcheng Zhang; Kangni Yan; Qunhua Peng; Shan Feng; Zhangfeng Zhao; Long Chen; Lin Ye; Jianyu Fu; Haipeng Lv; Dan Mu; Chunwang Dong; Zhi Lin; et al. (Food Chemistry, 2024)

GPX2 acts as an oncogene and cudraflavone C has an anti-tumor effect by suppressing GPX2-dependent Wnt/β-catenin pathway in colorectal cancer cells - Zhuo Wu; Su Zhou; Dan Liang; Lan Mu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Enhanced azo dye reduction at semiconductor-microbe interface: The key role of semiconductor band structure - Hefei Shi; Xinbai Jiang; Xiaojiao Wen; Cheng Hou; Dan Chen; Yang Mu; Jinyou Shen (Water Research, 2024)

Unveiling the biogeochemical mechanism of nitrate in the vadose zone-groundwater system: Insights from integrated microbiology, isotope techniques, and hydrogeochemistry - Dan Wang; Peiyue Li; Dawei Mu; Weichao Liu; Yinfu Chen; Misbah Fida (Science of The Total Environment, 2024)

An esterase activity-based biosensor for rapid and sensitive detection of viable Escherichia coli O157:H7 in milk - Xiaoyan Feng; Donggen Zhou; Dan Mu; Hengyi Xu (International Dairy Journal, 2023)

Vitamin D ameliorates Aeromonas hydrophila-induced iron-dependent oxidative damage of grass carp splenic macrophages by manipulating Nrf2-mediated antioxidant pathway - Hao Sun; Dan Wang; Jingqi Ren; Jiaxi Liu; Zhe Wang; Xinyan Wang; Anying Zhang; Kun Yang; Mu Yang; Hong Zhou (Fish & Shellfish Immunology, 2023)

Nitrification-denitrification co-metabolism in an algal-bacterial aggregates system for simultaneous pyridine and nitrogen removal - Xiaoyu Zhang; Dan Chen; Xinying Hou; Na Jiang; Yan Li; Shijian Ge; Yang Mu; Jinyou Shen (Journal of Hazardous Materials, 2023)

C21 steroids from the roots of Marsdenia tenacissima - Jin-Ling Liu; Hong-Tao Xu; Dan-Dan Mu; Xiao Han; Ting-Ting Du; Yong-li Wang; Xiao-Hui Wei; Gui-Xin Chou (Phytochemistry, 2023)

Opportunities and challenges in Asian bee research and conservation - Natapot Warrit; John Ascher; Parthib Basu; Vasuki Belavadi; Axel Brockmann; Damayanti Buchori; James B. Dorey; Alice Hughes; Smitha Krishnan; Hien T. Ngo; Paul Williams; Chao-Dong Zhu; et al. (Biological Conservation, 2023)

A prospective observational phase IV study on effectiveness of animal derived polyclonal antibody antivenoms against West African carpet viper (Echis romani) induced coagulopathy and mortality - Titus B. Dajel; Saidu B. Abubakar; Nasiru M. Dan-Amarya; Nyam A. Azi; Salisu Mu'azu; Muhammad Hamza; Garba Iliyasu; Muhammad Y. Gwarzo; Abdulrazaq G. Habib (Toxicon, 2023)

Preparation and characterization of carboxymethyl chitosan/nano-MgO/red cabbage anthocyanins multifunctional films via colloid formation and its application on shrimp preservation - Qiang Xie; Dan Luo; Kaiyu Mu; Wentong Xue (Food Packaging and Shelf Life, 2023)

Meso-macro constitutive model for frozen salinized sandy soil - Ling Chen; Honggang Zhang; Enlong Liu; Yanhu Mu; Baocun Yang; Dan Wang (Cold Regions Science and Technology, 2023)

Experimental study on the explosion destructive ability of magnesium powder/hydrogen hybrids in large space - Xinyu Xiong; Kai Gao; Jie Mu; Changquan Ji; Bin Li; Dan Zhang; Yadong Xu; Lifeng Xie (Process Safety and Environmental Protection, 2023)

Value-added utilization of hydroxy-substituted aromatics in coal-derived liquids - Zhi-Hao Ma; Sheng Li; Xue-Qian Dong; Cai-Xia Ju; Dan Mu; Zheng Yang; Min Li; Xian-Hou Guo; Zhi-Min Zong; Xing-Shun Cong; Xian-Yong Wei (Fuel, 2023)

Synthesis of spindle-like amino-modified Zn/Fe bimetallic metal-organic frameworks as sorbents for dispersive solid-phase extraction and preconcentration of phytohormoes in vegetable samples - Peige Qin; Dengke Chen; Dan Li; Mengyuan Li; Mengyao Mu; Yanmei Gao; Shiping Zhu; Minghua Lu (Food Chemistry, 2023)

Controllable assembly of three-dimensional porous graphene-Au dual aerogels and its application for high-efficient bioelectrocatalytic O2 reduction - Tuotuo Ma; Wenjing Mu; Yarui Tang; Wenhua Bi; Wei Liu; Dan Wen (Analytica Chimica Acta, 2023)

Developmental and reproduction toxicity studies of Biolimus A9 in SD rats - Shidong Qiu; Yang Liu; Yuanhang Pan; Yuji Liang; Liyuan Zhou; Xiaobo Wang; Peilu Sun; Suling Teng; Dan Wang; Yanling Mu (Reproductive Toxicology, 2023)

Study on derived hydrogen and ignition influencing factors of moist magnesium debris - Xinyu Xiong; Kai Gao; Jie Mu; Changquan Ji; Bin Li; Dan Zhang; Yadong Xu; Lifeng Xie (Fuel, 2023)

Failure mechanism and movement process of three loess landslides due to freeze-thaw cycle in the Fangtai village, Yongjing County, Chinese Loess Plateau - Jiaxu Kong; Jianqi Zhuang; Jianbing Peng; Penghui Ma; Jiewei Zhan; Jiaqi Mu; Jie Wang; Dan Zhang; Jia Zheng; Yuting Fu; Shibao Wang; Chenhui Du (Engineering Geology, 2023)

Hierarchically porous zirconium-based metal–organic frameworks for rapid adsorption and enrichment of sulfonamide antibiotics - Lizhen Han; Peige Qin; Mengyuan Li; Dan Li; Mengyao Mu; Yanmei Gao; Shiping Zhu; Minghua Lu; Zongwei Cai (Chemical Engineering Journal, 2023)

Benthic Sargassum composition and community characteristics in the intertidal zone of Hainan Island, China - Xiaoxiao Zou; Tian Meng; Dandan Yao; Zuo Chen; Jun Zhu; Dan Mu; Shixiang Bao (Marine Biology Research, 2022)

Stability evaluation for steep bank slope with microseismic monitoring in Three Gorges Reservoir area - Qing-ming Xie; Kui Long; Zi-mu Li; Li-chuan Chen; Hong Liu; Hong Xu; Fei He; Dan Liang; Xue-kun Xiang; Qiang Ma (Journal of Mountain Science, 2022)

Associations between species-level indoor microbiome, environmental characteristics, and asthma in junior high schools of Terengganu, Malaysia - Xi Fu; Yi Meng; Yanling Li; Xunhua Zhu; Qianqian Yuan; Aminnuddin Ma’pol; Jamal Hisham Hashim; Zailina Hashim; Gunilla Wieslander; Yi-Wu Zheng; Xu-Xin Lai; Michael Dho Spangfort; et al. (Air Quality, Atmosphere & Health, 2022)

Expression and functional analysis of cytoplasmic dynein during spermatogenesis in Portunus trituberculatus - Chao-Guang Wei; Dan-Li Mu; Dao-Jun Tang; Jun-Quan Zhu; Cong-Cong Hou (Cell and Tissue Research, 2021)

Maribacter hydrothermalis sp. nov., Isolated from Shallow-Sea Hydrothermal Systems Off Kueishantao Island - Huaying Lin; Dan Lin; Mu Zhang; Jianing Ye; Jia Sun; Kai Tang (Current Microbiology, 2021)

Correlation between single-nucleotide polymorphisms and statin-induced myopathy: a mixed-effects model meta-analysis - Qian Xiang; Xiao-Dan Zhang; Guang-Yan Mu; Zhe Wang; Zhi-Yan Liu; Qiu-Fen Xie; Kun Hu; Zhuo Zhang; Ling-Yue Ma; Jie Jiang; Yi-Min Cui (European Journal of Clinical Pharmacology, 2021)

Modeling the neuro-protection of theaflavic acid from black tea and its synergy with nimodipine via mitochondria apoptotic pathway - Dan Mu; Huaguang Qin; Mengjie Jiao; Shaogui Hua; Tingzhe Sun (Journal of Zhejiang University-SCIENCE B, 2021)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Poly-PR in C9ORF72-Related Amyotrophic Lateral Sclerosis/Frontotemporal Dementia Causes Neurotoxicity by Clathrin-Dependent Endocytosis - Rui Wang; Xingyun Xu; Zongbing Hao; Shun Zhang; Dan Wu; Hongyang Sun; Chenchen Mu; Haigang Ren; Guanghui Wang (Neuroscience Bulletin, 2019)

Association of TRIMCyp and TRIM5α from assam macaques leads to a functional trade-off between HIV-1 and N-MLV inhibition - Dan Mu; Jia-Wu Zhu; Feng-Liang Liu; Hong-Yi Zheng; Yong-Tang Zheng (Science China Life Sciences, 2018)

Analysis of the function of KIF3A and KIF3B in the spermatogenesis in Boleophthalmus pectinirostris - Yong-Qiang Zhao; Dan-Li Mu; Di Wang; Ying-Li Han; Cong-Cong Hou; Jun-Quan Zhu (Fish Physiology and Biochemistry, 2018)

Transcriptome analysis of alternative splicing in different moso bamboo tissues - Long Li; Qianqian Shi; Dan Hou; Zhanchao Cheng; Juan Li; Yanjun Ma; Xueping Li; Shaohua Mu; Jian Gao (Acta Physiologiae Plantarum, 2018)

Roles of flotillins in tumors - Xu-xu Liu; Wei-dong Liu; Lei Wang; Bin Zhu; Xiao Shi; Zi-xuan Peng; He-cheng Zhu; Xing-dong Liu; Mei-zuo Zhong; Dan Xie; Mu-sheng Zeng; Cai-ping Ren (Journal of Zhejiang University-SCIENCE B, 2018)

The acute toxicity of bisphenol A and lignin-derived bisphenol in algae, daphnids, and Japanese medaka - Dan Li; Ran Bi; Hongxing Chen; Lei Mu; Lina Zhang; Qin Chen; Haibo Xie; Yongju Luo; Lingtian Xie (Environmental Science and Pollution Research, 2017)

Expression of ethylene response factors (ERFs) From Betula platyphylla and the confer salt and drought tolerance analysis in a yeast - Wenhui Zhang; Guiyan Yang; Xuezhong Zou; Dan Mu; Hongyan Li; Dandan Zang; Yucheng Wang (Journal of Plant Biochemistry and Biotechnology, 2017)

Lipopolysaccharide suppresses human immunodeficiency virus 1 reverse transcription in macrophages - Feng-Liang Liu; Jia-Wu Zhu; Dan Mu; Yong-Tang Zheng (Archives of Virology, 2016)

Vascular endothelial growth factor-C protects heart from ischemia/reperfusion injury by inhibiting cardiomyocyte apoptosis - Xu-guang Chen; Yan-xia Lv; Dan Zhao; Lei Zhang; Fei Zheng; Jian-Ye Yang; Xiao-lin Li; Lu Wang; Lin-Yun Guo; Ya-mu Pan; Yu-wen Yan; Shi-You Chen; et al. (Molecular and Cellular Biochemistry, 2016)

Desulfurization of immobilized sulfur-oxidizing bacteria, Thialkalivibrio versutus, by magnetic nanaoparticles under haloalkaliphilic conditions - Xiaohui Xu; Yufeng Cai; Ziyu Song; Xiaoling Qiu; Jiemin Zhou; Yilan Liu; Tingzhen Mu; Dan Wu; Yueping Guan; Jianmin Xing (Biotechnology Letters, 2015)

Characterization of a d-psicose-producing enzyme, d-psicose 3-epimerase, from Clostridium sp. - Wanmeng Mu; Wenli Zhang; Dan Fang; Leon Zhou; Bo Jiang; Tao Zhang (Biotechnology Letters, 2013)

Sucrose treatment alters floral induction and development in vitro in gloxinia - Ming-Zhe Zhang; Li-Ling Wang; Dan Ye; Xi Chen; Zhi-Yi Wu; Xiao-Jia Lin; Wu-Jian Chen; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (In Vitro Cellular & Developmental Biology - Plant, 2012)

Mutations in exons of the CYP17-II gene affect sex steroid concentration in male Japanese flounder (Paralichthys olivaceus) - Ruiqin Ma; Feng He; Haishen Wen; Jifang Li; Bao Shi; Dan Shi; Miao Liu; Weijie Mu; Yuanqing Zhang; Jian Hu; Weiguo Han; Jianan Zhang; et al. (Journal of Ocean University of China, 2012)

Expression patterns of cytochrome P450 aromatase genes during ovary development and their responses to temperature stress in female yellow catfish (Pelteobagrus fulvidraco) - Miao Liu; Haishen Wen; Feng He; Jifang Li; Dan Shi; Jian Hu; Yuanqing Zhang; Ruiqin Ma; Weijie Mu; Baoxia Qi (Journal of Ocean University of China, 2011)

Numerical study of M2 internal tide generation and propagation in the Luzon Strait - Huan Li; Dan Song; Xueen Chen; Hongbao Qian; Lin Mu; Jun Song (Acta Oceanologica Sinica, 2011)

Activation of GH signaling and GH-independent stimulation of growth in zebrafish by introduction of a constitutively activated GHR construct - A. S. Ishtiaq Ahmed; Feng Xiong; Shao-Chen Pang; Mu-Dan He; Michael J. Waters; Zuo-Yan Zhu; Yong-Hua Sun (Transgenic Research, 2011)

Genetic polymorphism analysis of 15 STR loci in Chinese Hui ethnic group residing in Qinghai province of China - Ya-jun Deng; Bo-feng Zhu; Chun-mei Shen; Hong-dan Wang; Jing-feng Huang; Yuan-zhe Li; Hai-xia Qin; Hao-fang Mu; Jie Su; Jie Wu; Bo Zhang; Shuan-liang Fan (Molecular Biology Reports, 2011)

Overexpression of the cucumber LEAFY homolog CFL and hormone treatments alter flower development in gloxinia (Sinningia speciosa) - Ming-Zhe Zhang; Dan Ye; Li-Lin Wang; Ji-Liang Pang; Yu-Hong Zhang; Ke Zheng; Hong-Wu Bian; Ning Han; Jian-Wei Pan; Jun-Hui Wang; Mu-Yuan Zhu (Plant Molecular Biology, 2008)

A GIS-based research on the distribution of rural settlements in Yulin of northern Shaanxi - Zhao Mu-dan; Tang Guo-an; Shi Wen-zhong; Liu Yong-mei (Journal of Geographical Sciences, 2002)

Evaluation on the accuracy of digital elevation models - Tang Guo-an; Josef Strobl; Gong Jian-ya; Zhao Mu-dan; Chen Zhen-jiang (Journal of Geographical Sciences, 2001)